Enhancing Community Digital Health Literacy through Education and Assistance in the Use of Online Registration Applications for Health Services (JURNAL PENGMAS KESTRA (JPK), 2025)
Background: The digitalization of health services, including online registration systems, is a strategic effort to improve service efficiency and quality. Online registration applications allow patients to independently reserve services, obtain queue numbers, and reduce waiting times at healthcare facilities. However, the utilization of online registration applications remains low, including in Sekip Village, Lubuk Pakam District. Objective: This community service program aimed to enhance community digital health literacy through education and assistance in using online registration applications. Methode: The methods used included interactive lectures, demonstrations, and individual assistance to 45 participants. Evaluation was carried out through pre-tests and post-tests. This Community Service Program activity was carried out in Sekip Village, Lubuk Pakam District, Deli Serdang Regency, targeting productive age communities, the elderly, health service users, and community groups with limited digital literacy. Result: The results showed an increase in participants’ knowledge from an average of 48% (pre-test) to 87% (post-test). A total of 82% successfully downloaded the application independently, 71% created an account and logged in, and 67% completed a full registration simulation. Participants also demonstrated positive changes in perception, with 89% stating the activity was highly beneficial and 84% expressing their intention to use the application in future healthcare visits. This program effectively improved digital literacy, technical skills, and community readiness to adopt digital health services. The initiative contributes significantly to supporting digital health transformation at the community level.